(untitled) (Journal of University of Babylon for Engineering Sciences, 2021)
Housing is a key sector of any national economy, and is particularly important for urban development, Moreover, it is a vital issue in any government policy in all countries of the world, Despite the growing expectation that the private sector should play a very important role in financing low-income housing, the official financial sector is reluctant to finance low-income housing, especially in poor third world countries. Government financing policy for low income housing emphasizes the problem of affordability and funding sources, This paper addresses the evaluation of the government’s funding policy for low-income housing in Iraq, census data for the years 2016-2020 was used to analyze population indicators, Number of families, housing stock, housing supply, housing need and housing deficit, so to complete the analysis. This paper used the method of relative importance of housing stock, housing supply, housing need and housing deficit weighted by the number of families. The results were, the housing deficit recorded increasing rates of relative importance under the influence of population growth. While the relative importance of the housing supply does not meet the growing housing need. Therefore, government financing policies for low income housing were ineffective because they did not meet the growing housing need and did not fill the housing deficit.